2020
DOI: 10.1155/2020/8761485
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma for Treatment of Rheumatoid Arthritis: Case Series and Review of Literature

Abstract: Platelet-rich plasma (PRP) is an autologous blood product with platelets above circulating levels and releases several growth factors after activation. PRP may help to decrease joint inflammation by modulating synovial cell proliferation and differentiation and inhibition of catabolic pathways in various articular conditions. Though PRP has shown good efficacy in osteoarthritis and other musculoskeletal conditions such as synovitis, epicondylitis, skeletal muscle injuries, and tendinopathy, there is limited ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Starting with tendinopathies it has been tried in managing wound complications and as a means of postponing surgery in degenerative conditions like osteoarthritis of knee. [13][14][15] PRP is a cocktail with supraphysiological levels of platelets. 16 These when activated release a high concentration of various growth factors including but not limited to basic fibroblast growth factor, transforming growth factor, vascular endothelial growth factor, plateletderived growth factor, and epidermal growth factor among others.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with tendinopathies it has been tried in managing wound complications and as a means of postponing surgery in degenerative conditions like osteoarthritis of knee. [13][14][15] PRP is a cocktail with supraphysiological levels of platelets. 16 These when activated release a high concentration of various growth factors including but not limited to basic fibroblast growth factor, transforming growth factor, vascular endothelial growth factor, plateletderived growth factor, and epidermal growth factor among others.…”
Section: Discussionmentioning
confidence: 99%
“…Badsha et al recently revealed proof of concept of the immunomodulatory effects of PRP in four RA patients 54 ; ultrasound evidenced clinical improvement and amelioration of joint inflammation. A placebo-controlled trial in OA patients revealed a reduction in plasma concentrations of inflammatory and proangiogenic factors (investigative biomarkers) compared with controls.…”
Section: Mechanism Of Action Of Prp With a Focus On Inflammationmentioning
confidence: 96%
“…Albeit to a less documented extent than BM-MSCs, ADSCs have also shown a promising potential as a cell therapy for the treatment of immune system disorders, such as GVHD, Crohn's disease, psoriasis, and SS ( 282 285 ). Other cell-based therapies with less reported benefits in immune diseases include PRP, which has been shown to reduce pain and inflammation with ultrasound imaging evidence in patients with RA ( 286 ), and Tregs, which have been shown to reduce the incidence of acute GVHD ( 287 ). DCs are another type of immunotherapies exploited in the treatment of patients with immune system disorders.…”
Section: Clinical Benefits Of Cell Therapy By Select Fieldsmentioning
confidence: 99%